The role of caring staff in maintaining a proper nutritional status in demented long-term care patients - Babiarczyk, Beata; Kolonko, Jolanta (Nursing Problems / Problemy Pielęgniarstwa, 2008)
The risk of undernutrition increases significantly at elderly people. Different medical, social and environmental factors, can influence the change of the metabolism, absorption and cause the loss of the weight. A protein-energy malnutrition which is most common in geriatric patients is associated with deterioration of immune function, increased risk of pneumonia and pressure sores and those factors solely or together may cause a higher mortality. Demented patients are at great risk for undernutrition. The aim of this paper was to point at the psychosocial factors which could contribute to the maintaining an adequate nutritional status of demented patients. A proper organization of the meal times, serving aides for demented patients and an attractive milieu at meal times plays an important role in improving of food intake. In order to prevent the undernutrition, the caring staff should have appropriate knowledge and skills and treat every patient individually and holistically.